1998
DOI: 10.1046/j.1471-4159.1998.71010356.x
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Vesicle Protein SV2B, but Not SV2A, Is Predominantly Expressed and Associated with Microvesicles in Rat Pinealocytes

Abstract: Abstract:Microvesicles are endocrine counterparts of neuronal synaptic vesicles, and accumulate and secrete classic neurotransmitters. In mammalian pinealocytes, microvesicles accumulate L-glutamate through a vesicular glutamate transporter and secrete it through exocytosis. To characterize the molecular organization of microvesicles in more detail, we investigated in this study the expression and localization of synaptic vesicle protein 2 (SV2) in rat pinealocytes. RT-PCR analysis indicated that transcripts s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…The high sequence homology and the localization of these two isoforms with secretory granules points to their functional importance in hormone secretion. Like in the neuroendocrine pinealocytes (Hayashi et al, 1998), SV2B is only present on SLM in INS-1E cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The high sequence homology and the localization of these two isoforms with secretory granules points to their functional importance in hormone secretion. Like in the neuroendocrine pinealocytes (Hayashi et al, 1998), SV2B is only present on SLM in INS-1E cells.…”
Section: Discussionmentioning
confidence: 96%
“…The three SV2 isoforms are also differentially distributed in the mouse retina (Wang et al, 2003). Regarding the neuroendocrine cells, SV2A is detected in the cell line PC12 whereas SV2B is associated with microvesicles of rat pinealocytes (Bajjalieh et al, 1994;Hayashi et al, 1998). In adrenal chromaffin cells, SV2A is mainly localized to granules whereas SV2C is enriched on microsomes .…”
Section: Introductionmentioning
confidence: 99%
“…Because Rab proteins confer specificity to vesicles, these results indicate that "synaptic vesicle-like vesicles" function in trafficking and secretion in general tissues. Some recent studies reported that SV2B plays an important role in maintaining tissue-specific function (15)(16)(17)(18). The tissue-specific expression of SV2B suggests that SV2B plays a role in forming the tissuespecific structure.…”
Section: Discussionmentioning
confidence: 99%
“…SV2 was understood to be exclusively expressed in the neuronal tissue. However, some reports have shown that SV2s are expressed in several other tissues [51,52] . SV2B is detected in the microvesicles of pinealocytes.…”
Section: Sv2bmentioning
confidence: 99%
“…SV2B is detected in the microvesicles of pinealocytes. Both pinealocyte and podocyte are characterized by their specialized processes [52] . These properties also suggested that SV2B plays a role in the trafficking to the terminal of processes.…”
Section: Sv2bmentioning
confidence: 99%